Contrasting Dynamics of Democracy and Authoritarianism in Sub-Saharan Africa: Historical, Institutional, Judicial, and Sociopolitical Factors - Diallo, Boubacar Sidi diallo (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
This paper examines the current dual political system in Sub-Saharan Africa, where democracy exists side by side with some element of autocracy. It looks at the varying perspectives of history, institutions, judicial, and socio-political factors that all contribute towards influencing regimes’ outcomes across the region. Colonial and post-colonial eras have observed the birth of different state structures, often centralized, exclusionary, and resistant to diverse governance. These structures have played a significant role in nation building. The paper also explores how socio-political factors like international influence, economic backwardness/progress, and grassroots mobilization can play a part in shaping regime outcomes. Consequently, the paper explains the diverse political developments observed across African states, contributing to broader debates on governance, state legitimacy, and democratic transitions in postcolonial contexts.